Diagnostic Accuracy of a 3‐Point Ultrasound Protocol to Detect Esophageal or Endobronchial Mainstem Intubation in a Pediatric Emergency Department. (16th April 2019) - Mori, Takaaki; Nomura, Osamu; Hagiwara, Yusuke; Inoue, Nobuaki
Abstract : Objectives: The aim of this study was to evaluate the diagnostic accuracy of the 3‐point approach with ultrasonography for confirming endotracheal tube (ETT) placement in pediatric patients. Methods: This was a prospective study conducted at a tertiary care center in Japan between March 2014 and March 2016. Children aged 0 to 18 years requiring endotracheal intubation in our emergency department (ED) who underwent ultrasonography for confirming ETT placement were enrolled. Patients who had already undergone a tracheotomy or intubation before arrival at our ED or who had severe neck injuries hindering ultrasonography were excluded. Quantitative capnography and portable chest x‐ray imaging were used as the reference standard for the confirmation of proper ETT placement. The main outcome was the diagnostic accuracy of the 3‐point approach with ultrasonography for detecting inappropriate ETT placement. Results: In total, 68 patients were enrolled. The median age was 17 months (interquartile range, 8–40), and 51.4% were males. Three (4.4%) and 7 (10.3%) patients had esophageal and endobronchial mainstem intubation, respectively. The patients received emergency intubation due to a dysfunction of the central nervous system (45.6%) or respiratory failure (22.0%). The sensitivity and specificity of esophageal versus tracheal intubation was 100% (95% confidence interval [CI], 54.9%–100.0%) and 100% (95% CI, 97.9%–100.0%), respectively, whereas for endobronchial mainstem intubation versus tracheal intubation, the sensitivity and specificity was 85.7% (95% CI, 56.7%–96.0%) and 98.3% (95% CI, 94.8%–99.5%), respectively. Agreement between the reviewers was high (kappa coefficient, 0.78). Conclusion: The 3‐point approach with ultrasonography was a feasible method for detecting esophageal and endobronchial mainstem intubation in pediatric patients.